A comparative test of steam pipe coverings - Forest, Harry Verne (My University, 1900)
Introduction: To those unfamiliar with it, the subject of protecting steam pipes and heated surfaces from loss of heat must necessarily seem of small importance, for they are unaware of the great amount of heat that is lost from bare surfaces and the large proportion of it that can be saved by the use of a good covering. The average steam plant owner does not have this loss directly impressed upon himself. He may know there is one but he cannot easily determine its magnitude hence takes no precaution to arrest further loss. In some few situations where fuel is very cheap, and for certain classes of work it may happen that coverings would not be desirable; yet wherever the economical production and use of steam is of importance a good covering will prove one of the best investments that can be made. Its use in certain cases becomes necessary apart from any saving that would ensue where the radiation from bare pipes would make an engine room unbearable. Granting that coverings would prove a good investment, the would be purchaser is confronted by scores of manufacturers, making coverings of all conceivable materials and combinations of them supposed to have some insulating value. Each maker of coverings claims that his is the best and brings forth a report of some test in which his product shows the greatest efficiency of those tested. In most cases these results are open to question, being sometimes made by interested or at least not entirely unbiased persons, and in others due to defects in the methods of apparatus employed. The manufacturer never tests his covering except in competition with poorer ones. In some cases, while the results are perfectly reliable, the tests were made several years ago, in two instances fifteen and seventeen years, and the coverings have not been subjected to comparison with ones of later and perhaps improved manufacture.
Citation: Forest, Harry Verne. A comparative test of steam pipe coverings. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Steam Pipes; Engineering; Testing; Insulation; Theses